Nepal’s Consumer Court: Evolving Jurisprudence, Past Lessons and Future Directions (Sambahak: Human Rights Journal, 2025)
This paper examines the establishment, structure, and evolving jurisprudence of Nepal's Consumer Court system, inaugurated in 2025 following the Supreme Court's directive and provisions of the Consumer Protection Act, 2075 B.S. The research analyses the court's legal foundation, jurisdictional authority, and operational framework within Nepal's judicial landscape, where it functions on par with District Courts while addressing specialized consumer disputes. The study explores international consumer protection models from India, the United States, South Africa, and China to contextualize Nepal's approach and identify potential directions for improvement. Key case laws from Nepal and abroad are evaluated to understand emerging judicial interpretations of consumer rights. The paper concludes by assessing three critical dimensions of consumer justice: accessibility of legal remedies, protection of vulnerable consumers, and safeguarding economic interests, while emphasizing the importance of ethical business practices and good faith doctrine in commercial transactions. This analysis provides valuable insights into the challenges and opportunities for Nepal's newly established Consumer Court to effectively address consumer grievances and foster fair marketplace practices in an increasingly complex economic environment.